Respiratory distress in Holstein cows fed corn silage: case report - Sosa, Emiliano; Ricci, Patricia; Di Leo, C.; Lombardi, B.; Escapil, J.; Turcato, Adolfo; Crivella, R.; Canton, German Jose (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2023)
An outbreak of respiratory distress was observed in Holstein cows immediately after consuming a new batch of corn-silage, presumably due to the presence of pneumotoxic gases. Signs were observed in 10% of the cows, and characterized as tachypnea, orthopneic position, cough and notable anxiety a few minutes after offering the silage. No deaths were recorded. Mild leucocytosis was observed in the hemogram. Nutritional analysis and nitrate determination of the corn-silage revealed usual values. Nitrous oxide and methane concentration were evaluated by gas chromatography and nitrogen oxides concentration directly with a portable device, resulting in acceptable values. Although high concentrations of toxic gases could not be evidenced in the air sampled on farm, the clinical signs observed coincide with those reported in cases of exposure to gases formed during corn silage processes. A greater emphasis is required in the evaluation of the corn to be ensiled, given the possible existence of factors that can generate the accumulation of potentially toxic gases for cattle that affect negatively their health and productivity.